ANALISIS KESADARAN MASYARAKAT PASCA KEGIATAN PEMBERSIHAN OLEH PANDAWARA GROUP DI PANTAI LOJI - Muhammad Alfin Gilang; Bagus Sugiarto; Nathaniel Septian Prasmono; Dyah Cahayasari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the financial performance of PT Indonesia Paradise by utilizing liquidity and profitability ratios over the 2021-2023 period. The primary issue faced by the company is the declining trend in financial ratios, which could potentially hinder the company's operational sustainability. A quantitative approach was employed in this research, with secondary data obtained from financial statements PT Indoenesia Paradise such as balance sheets and income statements, complemented by a literature review. The data were analyzed using descriptive analysis and financial ratio analysis methods using Microsoft exel. The results indicate significant declines in liquidity ratios, including the current ratio, quick ratio, and cash ratio, particularly in 2023, which fell below industry standards. Similarly, profitability ratios such as net profit margin and return on equity showed a downward trend, reflecting reduced efficiency in generating profits. These trends highlight challenges in maintaining financial stability and operational performance. The study concludes that PT Indonesia Paradise needs to improve its cash management, enhance cost control measures, and adopt more effective operational strategies. These steps are critical to reversing the downward trends, improving financial performance, and ensuring the company's long-term sustainability in a competitive industry.